(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Students’ learning attitudes have been widely believed to be able to affect their learning outcomes. The paper examines Vietnamese students’ attitudes towards learning English for Specific Purposes (ESP) at the tertiary level. It also considers factors influencing their attitudes towards learning ESP. A questionnaire of 50 items was utilized to collect data from 251 non-English majored students. The research results revealed that the participants had favorable attitudes towards learning ESP in general and even towards factors in the ESP learning process such as teachers, classroom environment, course books and tests. Moreover, the findings indicated teachers had the most influential effect on the students’ attitudes to ESP learning, while tests had the least influential one. Some pedagogical implications can be drawn from the research results for the improvement of students’ learning attitudes and ESP learning outcomes.